Mining for osteogenic surface topographies: In silico design to in vivo osseo-integration. (August 2017) - Hulshof, Frits F.B.; Papenburg, Bernke; Vasilevich, Aliaksei; Hulsman, Marc; Zhao, Yiping; Levers, Marloes; Fekete, Natalie; de Boer, Meint; Yuan, Huipin; Singh, Shantanu; Beijer, Nick; Bray, Mark-Anthony; et al.
Abstract: Stem cells respond to the physicochemical parameters of the substrate on which they grow. Quantitative material activity relationships – the relationships between substrate parameters and the phenotypes they induce – have so far poorly predicted the success of bioactive implant surfaces. In this report, we screened a library of randomly selected designed surface topographies for those inducing osteogenic differentiation of bone marrow-derived mesenchymal stem cells. Cell shape features, surface design parameters, and osteogenic marker expression were strongly correlated in vitro . Furthermore, the surfaces with the highest osteogenic potential in vitro also demonstrated their osteogenic effect in vivo : these indeed strongly enhanced bone bonding in a rabbit femur model. Our work shows that by giving stem cells specific physicochemical parameters through designed surface topographies, differentiation of these cells can be dictated.